MAPPING FIQH SIYASI: Islamis Versus Sekularis Dan Khilafah Versus Nation States - Toriquddin, Moh. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The current discussions of Fiqh siyasah are still interesting topic tobe discussed. These debate using a comparative method such as Islamic politic theories which are â€œvis to visâ€secularand khilafah of vis to vis nation states. Surely, it is hoped, may open the character and unique of Fiqh siyasah itself. Islamic thoughts globallyare based on the politic theories such as:Â Â religious obligation which was done by Rasulullah Saw. Then, God (Allah) should be the only sovereignty and obey the ruler is necessary as well.Secular thoughts, however, are basedon the politic theories such as: ratio.Furthermore, shape of nation can determine anything, the people hold the power, and the president have responsible for people. The system of Islamic politic is a system of khilafah which is exists since the period of Muhammad SAWleaving for Madinah until the downfall of khilafah in Turki. After that, many Moslems Nations graduallyadopt democration as their government system.